2015
DOI: 10.2217/fon.15.190
|View full text |Cite
|
Sign up to set email alerts
|

Management of Periorbital Basal Cell Carcinoma with Orbital Invasion

Abstract: Basal cell carcinoma (BCC) is the most common eyelid malignancy; however, orbital invasion by periocular BCC is rare, and management remains challenging. Established risk factors for orbital invasion by BCC include male gender, advanced age, medial canthal location, previous recurrences, large tumor size, aggressive histologic subtype and perineural invasion. Management requires a multidisciplinary approach with orbital exenteration remaining the treatment of choice. Globe-sparing treatment may be appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 33 publications
3
66
0
3
Order By: Relevance
“…Eye-sparing surgery has been previously suggested in selected cases 8. Madge et al reported their experience with 20 patients with locally advanced medial canthal BCC with orbital invasion and focused on the desired surgical technique for achieving clear margins while sparing the eye 9.…”
Section: Discussionmentioning
confidence: 99%
“…Eye-sparing surgery has been previously suggested in selected cases 8. Madge et al reported their experience with 20 patients with locally advanced medial canthal BCC with orbital invasion and focused on the desired surgical technique for achieving clear margins while sparing the eye 9.…”
Section: Discussionmentioning
confidence: 99%
“…A visible or palpable mass was observed in only 35.7% patients, with no bone fixation and no orbital signs. Other possible symptoms included immobile lids, epiphora (secondary to canalicular or nasolacrimal sac involvement) and ptosis 6,14…”
Section: Clinical Investigationmentioning
confidence: 99%
“…The morpheaform, infiltrating and basosquamous subtypes of BCC are more aggressive but rare (making up only 5%–7% of all cutaneous BCCs), and have a higher rate of residual positive margins after excision, as well as a larger risk of recurrence and metastasis. Consequently, in cases of BCC with orbital invasion, these aggressive subtypes make up >80% of cases 6,14. BCC usually presents as a single lesion with ulceration, or central scarring and peripheral keratosis, with even deep infiltration 3.…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Más del 20 % de los CBC se produce alrededor de los ojos, de los cuales más de la mitad se presentan en el párpado inferior, un tercio en el canto medial, un 15 % en el párpado superior y un 5 % en el canto lateral (30)(31)(32).…”
Section: Carcinoma Basocelular (Cbc)unclassified